Application of the immunoperoxidase monolayer assay to characterize non-cytopathic bovine viral diarrhea virus of Indonesian isolates - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
The approach of the immunoperoxidase monolayer assay (IPMA) was used to characterize 2 different fragments of nonÂ¬cytopathic bovine viral diarrhea virus (NCP-BVDV) genes of Indonesian strains, isolated in the Immunochemistry/Chemistni Laboratory at Inter University Center for Biotechnology, Gadiah Mada University, Yogyakarta, Indonesia. Each strain was tested for reactivity with a monoclonal antibody (MoAb) specific for two different regions within the gene coding for protein p80 and within the envelope glycoprotein (gp53) region. The results indicated that only one NCP-BVDV of Indonesian isolate, designated 650 strain which reacts with the p80 and all of the gp53 specific MoAbs. Whereas, others had a different pattern of reactivity with MoAbs tested. The variability of the NCP-BVDV reaction against MoAbs used in the present study may reflect in their antigenic variability.